FEED MANAGEMENT AND MOLASSES APPLICATION ON THE INTENSIVE MILKFISH CULTURE (Chanos chanos Forsk.) IN PONDS - Brata Pantjara; Erfan Andi Hendrajat; Anang Hari Kristanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
The problems faced in the intensive milkfish culture were the high and expensive feeds requirement. To overcome the problem, it needs the optimization of feed management with application of molasses for producing of bioflocs in pond. Bioflocs were a biomass set of heterotrophic bacteria, protozoa, plankton, and organic particle. The purpose of this research was to know the influence of feed management and application of molasses on the intensive culture of milkfish in ponds. The study was conducted in brackishwater pond with 2,500 m2 size; conducting at experimental pond installation, Research and Development Institute for Coastal Aquaculture, Maros. The treatments of this research were without reduction commercial feeds as control (A); 10% reduction of commercial feed and molasses application (B); and 20% reduction of commercial feed and molasses application (C). Reduction of commercial feed was as many as 10% and 20% of the feed given doses of each application. The results of this research showed that intensive milkfish culture with biofloc was not significantly increase of the growth and production of milkfish. The highest of milkfish production was obtained in A treatment with 7,260 kg/ha; followed by B (6,339 kg/ha) and the lowest was in C (5,780 kg/ha).